ROS-mediated membrane damage and antioxidant imbalance drive apple flesh browning during cold storage - Wang, Jihan; Li, Fujun; Li, Bingru; Li, Ling; Shang, Jing; Fu, Xiaodong; Zhao, Xiuming; Li, Xiaoan; Zhang, Xinhua; Ahmed, Zienab F. R. (Frontiers in Plant Science, 2025)
IntroductionFlesh browning is a major postharvest disorder in apples during cold storage, yet its physiological basis remains unclear. This study examined reactive oxygen species (ROS) metabolism and antioxidant systems in flesh-browning (FB) and normal (FN) tissues of browning apples, compared with healthy fruit (Control). Methods‘Fuji’ apples were stored at −1-0°C for 120 days. Flesh color, membrane damage indicators, phenolic metabolism, antioxidant contents (AsA, GSH), ROS levels (H2O2, O2•-), and antioxidant enzyme activities (SOD, CAT, APX) were analyzed, together with relevant gene expression. ResultsFB tissues showed the highest PPO and POD activities, enhanced membrane damage (higher EC, MDA, LOX), and markedly elevated ROS. Total antioxidant capacity decreased by ~25% in FB, accompanied by significant reductions in AsA and GSH and lower CAT/APX activities. Although phenylpropanoid-related enzymes and genes were upregulated, the resulting phenolics and flavonoids were insufficient for ROS mitigation. Strong correlations were found between browning intensity (a*), ROS accumulation, membrane damage, and antioxidant depletion. DiscussionProlonged cold storage induces severe ROS accumulation and membrane disruption in FB tissues. Simultaneous reductions in non-enzymatic antioxidants (AsA/GSH) and antioxidant enzymes (CAT/APX) create a self-reinforcing imbalance in ROS metabolism, ultimately triggering enzymatic browning.